Sustaining factors for lean manufacturing excellence : an explanatory mixed methods study - Norhana, Mohd Aripin (2023)
In today's market, manufacturers face challenges in quality, flexibility, costs, and productivity. To stay competitive, the manufacturing industry must enhance processes to maximize value and reduce waste. Therefore, lean manufacturing implementation is crucial for survival in today’s competitive market. However, figures indicate that not all manufacturers have effectively implemented lean practices to improve their organizational performance. This sequential explanatory mixed methods study aims at investigating the sustaining factors of lean manufacturing implementation among medium and large discrete manufacturers in Malaysia while scrutinizing the role of manufacturing maturity in strengthening the effects of lean manufacturing implementation on manufacturing excellence. The result interpretation from quantitative and qualitative concluded that lean knowledge management, lean culture, lean leadership, lean supplier management strengthen lean manufacturing implementation, while lean resource management does not strengthen its implementation. The results indicate that initially, lean manufacturing implementation does not have a direct impact on reducing production costs. However, the effects become significant when the implementation mature along the learning curve. This study is hoped to expand the boundary of the existing literature and contribute to the body of knowledge while providing insights to practitioners in tailoring strategies to sustain lean manufacturing implementation and leverage their manufacturing excellence. As a recommendation for future researchers, it is suggested to investigate lean technology, integration of management systems, and research and development involvement as sustaining factors for lean manufacturing implementation.